We Will Tell You The Representation Of Family Communication In Today's Film: Analysis Of Semiotics Roland Barthes - Panggabean, Alya Hamzah; Simamora, Irma Yusriani (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Movies are one of the effective ways to represent the dynamics of family relationships. In addition to serving as entertainment, movies can also depict various social issues, one of which is family communication that is full of challenges. The purpose of the research was to analyze how family communication is represented in the film "Today We Will Tell Later" using Roland Barthes' semiotic approach. This study uses a descriptive qualitative research method, which emphasizes more on the process of deductive and inductive inference. The source of the data taken comes from the film Today We Will Tell Later which will be analyzed thoroughly. The researcher analyzed the signs contained in the film using Roland Barthes' semiotic approach which included denotative, connotative, and mythical levels. The results of the study show that the film Today Will We Tell Later presents family values raised from Islamic views.